2020
DOI: 10.17645/pag.v8i1.2505
|View full text |Cite
|
Sign up to set email alerts
|

Leadership as Interpreneurship: A Disability Nonprofit Atlantic Canadian Profile

Abstract: The entrenchment of the neoliberal state and rise of populist leaders has marginalized the role of voluntary organizations in society. This presents significant challenges for nonprofit leaders in economically challenged areas as it erodes their ability to protect and serve vulnerable populations. Attention turns to maintaining hard fought gains at the expense of making progress. Yet doing so requires new skills and leadership styles to manage organizational change where innovation and transformation are key. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The existence of a figure village chief with a creative leadership pattern, intense assistance in training, and transforming knowledge and skills were expected to empower the PwSAs [29] and reduce their economic dependency [64]. The chief village conducts skills training and entrepreneurship education intensively and wholeheartedly.…”
Section: Entrepreneuring Pwsas Before and During The Pandemicmentioning
confidence: 99%
“…The existence of a figure village chief with a creative leadership pattern, intense assistance in training, and transforming knowledge and skills were expected to empower the PwSAs [29] and reduce their economic dependency [64]. The chief village conducts skills training and entrepreneurship education intensively and wholeheartedly.…”
Section: Entrepreneuring Pwsas Before and During The Pandemicmentioning
confidence: 99%
“…Interpreneurship adalah spirit kewirausahaan yang dilandasi semangat kolaborasi antarorganisasi dengan menjadikan inovasi dan transformasi berdasarkan warisan kultural dan modal sosial organisasi sebagai pijakan utama. Interpreneurship merupakan mekanisme perjuangan kelompok marginal untuk bertahan dan melakukan perubahan sosial ketika pemerintah dikendalikan oleh pemimpin populis dalam sistem neoliberal (Levesque, 2020). Pemimpin populis adalah model kepemimpinan yang di dalamnya pengambilan keputusan sepenuhnya didasarkan pada suara publik.…”
Section: Makna Kreatifitas Inovasi Dan Interpreneurshipunclassified
“…These have been developed primarily on for-profit organisations in the leadership theory domain (Osula and Ng 2014). Additionally, leadership in the for-profit sector has traditionally been the basis for understanding leadership in the non-profit sector (Levesque 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, more recently, the multidirectional management (Levesque 2020) required in non-profits is very different to for-profit leaders, with CEOs managing up to boards, managing down to staff and clients, and out to stakeholders, including government agencies, donors, community, and with other non-profits collaboratively, often in advocacy roles. Pertinent to the research reported herein is Levesque's (2020) suggestion that leaders in the disability service sector must develop more creative and innovative programs to respond to client needs. This level of creativity must result from refocusing the capabilities within these organisations to compete effectively in a more open marketplace, enabling non-profit service providers the ability to effectively position themselves in a competitive environment.…”
Section: Literature Reviewmentioning
confidence: 99%